E-Dictionary of Basic Kecak Dance Based on Bisindo in SBdP Subjects for Deaf Students - I Putu Agus Andi Myana Putra; Anak Agung Gede Agung; Chindytia (Jurnal Pedagogi dan Pembelajaran, 2025)
This research is motivated by the low dancing skills of deaf students due to the absence of learning media that are in accordance with their characteristics and learning styles. This research aims to develop learning media in the form of a E-Dictionary of basic Kecak dance based on Bisindo that is valid, feasible, and effective for use by deaf students. This research uses a development research approach with a systematic ADDIE model. The subjects involved included learning content experts, instructional design experts, learning media experts, and 9 deaf students in grade V elementary school. The results of the design expert assessment were 93.18% with very good qualifications, the results of the content expert assessment were 96.67% with very good qualifications, the results of the instructional design expert assessment were 95% with very good qualifications, the results of the media expert assessment were 95% with very good qualifications, the results of the individual trial were 92.35% with very good qualifications, the results of the small group trial were 95.83% with very good qualifications. The effectiveness test results obtained a tcount value of 23.056 while the ttable was 2.306, so H0 was rejected and H1 was accepted. So, it can be concluded that the E-Dictionary of basic Kecak dance based on Bisindo media effectively supports dance learning for deaf students. The implication is that this media can be an alternative tool in an innovative learning process to improve the skills of deaf students, while introducing them to local culture.